PENGARUH EKSTENSIFIKASI PAJAK DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI TERHADAP TINGKAT PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI TAHUN 2015-2019 - Ni Wayan Windariyanti (UNHI Press, 2021)
This study aims to determine the effect of tax extensification and individual taxpayer compliance on the level of individual income tax revenue. The research design used is quantitative research. The sampling technique used in the study was purposive sampling, with a total sample of 60 data. The data source in this research is secondary data. Data were collected using the method of literature study, archival research and observation. The data analysis method used is multiple linear regression analysis. The results showed that tax extensification had no effect on the level of personal income tax revenue. Individual taxpayer compliance has a positive and significant effect on the level of individual income tax revenue. Tax extensification and individual taxpayer compliance simultaneously have a positive and significant effect on the level of individual income tax revenue at the East Denpasar Primary Tax Service Office and the Denpasar City Social Service